Management of Cancer-Associated Thrombosis: Unmet Needs and Future Perspectives - Falanga, Anna; Le Gal, Grégoire; Carrier, Marc; Abdel-Razeq, Hikmat; Ay, Cihan; Martin, Andrés J. Muñoz; Rocha, Ana Thereza Cavalcanti; Agnelli, Giancarlo; Elalamy, Ismail; Brenner, Benjamin (TH Open, 2021)
Patients with cancer are at a high risk of symptomatic venous thromboembolism (VTE), which is a common cause of morbidity and mortality in this patient population. Increased risk of recurrent VTE and bleeding complications are two major challenges associated with therapeutic anticoagulation in these patients. Long-term therapy with low-molecular-weight heparins (LMWHs) has been the standard of care for the treatment of cancer-associated VTE given its favorable risk–benefit ratio in comparison with vitamin K antagonists. Direct oral anticoagulants (DOACs), which offer the convenience of oral administration and have a rapid onset of action, have recently emerged as a new treatment option for patients with cancer-associated thrombosis (CT). Randomized clinical trial data with head-to-head comparisons between DOACs and LMWHs showed that overall, DOACs have a similar efficacy profile but a higher risk of bleeding was observed in some of these studies. This review aims to identify unmet needs in the treatment of CT. We discuss important considerations for clinicians tailoring anticoagulation (1) drug–drug interactions, (2) risk of bleeding (e.g., gastrointestinal bleeding), (3) thrombocytopenia, hematological malignancies, (4) metastatic or primary brain tumors, and (5) renal impairment. Additional research is warranted in several clinical scenarios to help clinicians on the best therapeutic approach.
Keywords: cancer; thrombosis; DVT; VTE; PE; thrombocytopenia; LMWH; DOACs